2012
DOI: 10.1007/s12031-012-9880-8
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Long Noncoding RNAs in Autistic Brain

Abstract: The autism spectrum disorders (ASD) have a significant hereditary component, but the implicated genetic loci are heterogeneous and complex. Consequently, there is a gap in understanding how diverse genomic aberrations all result in one clinical ASD phenotype. Gene expression studies from autism brain tissue have demonstrated that aberrantly expressed protein-coding genes may converge onto common molecular pathways, potentially reconciling the strong heritability and shared clinical phenotypes with the genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 22 publications
4
132
0
Order By: Relevance
“…Dharap et al found 62 stroke-responsive lncRNAs showing 90% sequence homology with exons of protein-coding genes in their study on lncRNA expression profiles in focal ischemia (35). Similarly, Ziats et al reported that most differentially expressed lncRNAs in autism spectrum disorders (ASD) were from intergenic regions (~60%), from antisense to proteincoding loci (~15%), or within introns of protein-coding genes (~10%), with the others representing overlapping transcripts from exons or introns in both sense and antisense directions (36). Another complicating factor is the presence of bifunctional RNAs, which are transcripts that function as non-coding transcripts under certain conditions and are translated into functional proteins in other situations (37,38).…”
mentioning
confidence: 96%
“…Dharap et al found 62 stroke-responsive lncRNAs showing 90% sequence homology with exons of protein-coding genes in their study on lncRNA expression profiles in focal ischemia (35). Similarly, Ziats et al reported that most differentially expressed lncRNAs in autism spectrum disorders (ASD) were from intergenic regions (~60%), from antisense to proteincoding loci (~15%), or within introns of protein-coding genes (~10%), with the others representing overlapping transcripts from exons or introns in both sense and antisense directions (36). Another complicating factor is the presence of bifunctional RNAs, which are transcripts that function as non-coding transcripts under certain conditions and are translated into functional proteins in other situations (37,38).…”
mentioning
confidence: 96%
“…In a lncRNAs transcriptome study of post-mortem brain tissue of ASD patients [63], 222 differentially expressed lncRNAs between ASD and controls were identified, with an enrichment of genes associated with neuronal migration. It should be cautioned that the sample size was small with only 2 patient samples with 2 controls in this study.…”
Section: Long Non-coding Rnas (Lncrnas) In Asdmentioning
confidence: 99%
“…Profiling lncRNAs in the nucleus accumbens of cocaine-conditioned mice, an animal model that exhibits aberrant plasticity, revealed hundreds of differentially expressed lncRNAs, including those associated with plasticity-related genes [44]. lncRNAs are similarly deregulated in relevant human neuropathological specimens from patients with alcohol and heroin addiction, as well as other disorders characterized by abnormal plasticity, such as autism and intractable epilepsy [45][46][47][48]. Many of these lncRNAs are linked with genes that have key roles in longterm potentiation, synaptic activity and memory, such as brainderived neurotrophic factor (BDNF) and activity-regulated cytoskeleton-associated protein.…”
Section: Brain Developmentmentioning
confidence: 99%
“…These include, as examples, lncRNA signatures in neuropathological specimens from patients with AD [86], addiction to alcohol [46], addiction to heroin [45], autism [47], gliomas [87,88], Huntington's disease [89], and pituitary adenomas [90]. Importantly, these abnormal expression patterns are not only found in brain but they can also be present in more accessible fluids and tissues.…”
Section: Establishing Paradigms For Lncrna-related Pathologymentioning
confidence: 99%